Make PCI great again: Come on USA, catch up with the rest of the world. Issue 5 (6th November 2017) - Heuser, Richard
Key Points: Same day discharge after PCI lags in the USA The radial approach to PCI reduces complications compared to the femoral approach USA physicians need to seize the opportunity to not only perform PCI safely, but with economic responsibility